2021
DOI: 10.3389/fimmu.2021.674643
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Bacterial and Host Factors Involved in the Interaction of Mycobacterium bovis with the Bovine Innate Immune Cells

Abstract: Bovine tuberculosis is an important animal and zoonotic disease caused by Mycobacterium bovis. The innate immune response is the first line of defense against pathogens and is also crucial for the development of an efficient adaptive immune response. In this study we used an in vitro co-culture model of antigen presenting cells (APC) and autologous lymphocytes derived from peripheral blood mononuclear cells to identify the cell populations and immune mediators that participate in the development of an efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…In a previous study, we had demonstrated that, unlike the attenuated Mb534 isolate, the virulent Mb04-303 strain induced the proliferation of interferon-gamma producer-natural killer (NK) cells when naive bovine PBMC was infected in vitro [ 4 ]. In addition, this innate immune response effectively controlled the intracellular replication of Mb04-303 in macrophages.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In a previous study, we had demonstrated that, unlike the attenuated Mb534 isolate, the virulent Mb04-303 strain induced the proliferation of interferon-gamma producer-natural killer (NK) cells when naive bovine PBMC was infected in vitro [ 4 ]. In addition, this innate immune response effectively controlled the intracellular replication of Mb04-303 in macrophages.…”
Section: Resultsmentioning
confidence: 99%
“…For the RNA-seq analysis, we selected samples from three different animals infected with Mb04-303 or Mb534 that met this criterion. We have previously demonstrated that in the absence of non-adherent cells, such as lymphocytes, infected macrophages failed to control the intracellular replication of Mb04-303 [ 4 ]. For this reason, the transcriptional analysis of infected macrophages cultured alone was excluded from this study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations